A left-sided cerebrospinal fluid hydrothorax and a right ventricular-peritoneal shunt: a unique clinical case study. Issue 9 (20th September 2019) - Hopkins, David; Pattman, Stewart; Jones, Rhian; Aujayeb, Avinash
Abstract : We describe the case of a 84-year-old woman with a right ventricular-peritoneal shunt and a left-sided pleural effusion, the analysis of which was positive for cerebrospinal fluid. We consider the potential causative mechanisms. Our patient was managed conservatively due to her frailty, the effusion being asymptomatic and her preference not to pursue further invasive diagnostic testing. This case report is unique due to the contralateral nature of the effusion to the shunt, which has not been described before in the literature.